Strategi marketing public relations genio Untuk mempertahankan brand awareness Melalui influencer endorsement - Fahmi Wijayanto; RR Roosita Cindrakasih; Rizky Hidayat (CV Edujavare Publishing, 2025)
His study aims to analyze the marketing public relations strategy implemented by Genio in maintaining brand awareness through influencer endorsement. This research employs a qualitative method with a descriptive approach through in-depth interviews, observation, and documentation. The findings indicate that Genio's marketing public relations strategy focuses on the Three Ways Strategy, consisting of Pull, Push, and Pass Strategies. In the Pull Strategy, Genio utilizes influencer endorsement to convey product information through storytelling content. In the Push Strategy, Genio provides exclusive discount codes through influencers to encourage audience purchases. Lastly, in the Pass Strategy, Genio builds relationships with the audience through a content- based campaign called